THE EFFECT OF LEARNING MODELS DISCOVERY HELPFUL LAB VIRTUAL AGAINST THE ABILITY TO UNDERSTAND PHYSICS CONCEPTS - Sihombing, Joel Pebrian; Hutahaean, Juniar (IPER (Indonesian Physics Education Research), 2022)
This study aims to (1) determine student activity during the learning process using the Virtual Lab-assisted Discovery learning model on the subject matter of work and energy, (2) determine the effect of the Virtual Lab-assisted Discovery learning model on students' ability to understand physics concepts on the subject matter of effort and energy in class X semester II SMA Sw. Dharma Bhakti Siborongborong Academic Year 2022/2023.This type of research is quasi-experimental. The population in this study were all students of class X SMA Sw. Dharma Bhakti Siborongborong in even semester T.A. 2022/2023. The sample for this research was taken from two classes, namely class X IPA 1 (as the experimental class) and class X IPA 2 (as the control class), each of which consisted of 22 students and 20 students who were determined by the Cluster Random Sampling technique. Then given a different treatment, the experimental class using the Discovery Learning model assisted by the Virtual Lab and the control class with conventional learning. The data used in this study used a description test, the number of questions was 21 items which had been validated by the validator.From the research results, it was obtained that the average pretest value for the experimental class was 45.54 and for the control class was 43.81. After learning was completed, the posttest was given with the average result for the experimental class was 78.14 and the control class was 72.62. The data analysis technique used is the t test after the data is normally distributed and homogeneous. Based on data analysis and hypothesis testing, it was found that there was a significant influence of the Virtual Lab-assisted Discovery learning model on students' ability to understand physics concepts on the subject matter of work and energy.